An empirical assessment of alternative exchange rate regimes in medium term in Albania - Tonin Kola; Elida Liko (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2008)
This paper examines the alternative exchange rate regimes and their feasibility to be applied in Albania in medium term. In all empirical work done until now is been found a very low relationship between money and inflation in Albania before and after using the indirect instruments of monetary control. As a result, the motivation for finding other strategies for monetary policy and exchange rate policy is strong and has opened the debate of practitioners in this field. We argue that moving from freely floating exchange rate regime and informal IT strategy in formal IT strategy would be a more preferable strategy that will deal better with the fragile sustainability of current account deficit in Albania but not without problems to be applied.
Keywords: 330; Fester Wechselkurs; Optimaler Währungsraum; Währungssubstitution; Euro; Inflation Targeting; Albanien